PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN STRATEGI BELAJAR TUNTAS UNTUK MENINGKATKAN HASIL BELAJAR FISIKA MATERI HUKUM NEWTON DAN PENERAPANNYA DI KELAS X - Stefany Margareta Martono (SOSCIED, 2019)
Development Device with Mastery Learning Strategy to Improve Learning Outcomes Physics and Implementation of the Newton's Law in class X. The development is one way to create new innovations in learning activities in the classroom. The purpose of this research is 1) To get the proper and purposeful learning, combined with mastery learning strategies to improve learning outcomes in the material physics of Newton's laws in class X. 2) For the effectiveness of the learning device combined with mastery learning strategies to improve student learning outcomes on Newton's laws of matter in class X. this study uses a "research and development" following the stage of research and development according to Brog Gall. The sampling technique is done randomly, by drawing a coin. Subject trials consisted of testing the theoretical and empirical testing. Theoretically trial consists of three people, divided into 2 as a learning device design expert and one person as a theorist in the field of physics. For the empirical test consists of 10 people to test a small group of 20 people for field trials and 30 people for operational testing. The instrument used in this study were interviews, questionnaires, process assessment, achievement test. The data were analyzed with descriptive analysis and different test average with α=0,5. The results showed that the test for the development of this product 1) the development of good learning device and makes students focus on the material. 2) effective learning tools used in the classroom that can be seen from the average increase in higher learning outcomes physics experimental group than the control group.